The Influence of Work Experience and Training on Employee Performance at PT. Rubber Indonesia - Aldi, Deni Leo; Jamaludin, Asep; Nandang, Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
Due to process errors that occurred, PT Rubber Indonesia employees experienced a decline in performance, which resulted in products not meeting standards, customer complaints and decreased productivity. Some employees do not understand the company's Standard Operating Procedures (SOP) and Work Instructions (IK), which causes problems in the work process. This research aims to determine how work experience and training influence employee performance. This study used quantitative methods, and the sample consisted of 75 people who were selected purposively. Multiple linear regression analysis was carried out after the data was collected through distributing questionnaires. The results show that, while H1 is accepted, work experience has a significant effect on employee performance, H2 is rejected, training has no significant effect on employee performance. However, H3 is accepted, both work experience and training have a significant effect on employee performance. The results suggest that businesses should consider and leverage employee work experiences to improve performance and re-evaluate training programs to ensure that they are helping employees and the organization as a whole.